2021
DOI: 10.1111/all.15014
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of exposure to chlorination by‐products in swimming pools

Abstract: Concerns have been raised regarding the potential negative effects on human health of water disinfectants used in swimming pools. Among the disinfection options, the approaches using chlorine-based products have been typically preferred. Chlorine readily reacts with natural organic matter that are introduced in the water mainly through the bathers, leading to the formation of potentially harmful chlorination byproducts (CBPs). The formation of CBPs is of particular concern since some have been epidemiologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 139 publications
0
11
0
Order By: Relevance
“…Chlorine bleach or sodium hypochlorite is the most used disinfecting and cleaning agent, and chlorine disinfection‐by‐products (DBPs), such as chlorine or trichloramine, are irritants to the respiratory tract and are also associated with acute lung injury 46 . A recent position paper on the evidence of the health effects of acute and chronic exposure to swimming pools suggested that early and chronic exposure to DBPs may be associated with a higher risk of childhood asthma 47 . Taken together the evidence supports a growing call for mitigation and prevention actions on the role of cleaning and consumer products on childhood asthma.…”
Section: Environmental Pollutants As Determinants Of Childhood Asthmamentioning
confidence: 99%
“…Chlorine bleach or sodium hypochlorite is the most used disinfecting and cleaning agent, and chlorine disinfection‐by‐products (DBPs), such as chlorine or trichloramine, are irritants to the respiratory tract and are also associated with acute lung injury 46 . A recent position paper on the evidence of the health effects of acute and chronic exposure to swimming pools suggested that early and chronic exposure to DBPs may be associated with a higher risk of childhood asthma 47 . Taken together the evidence supports a growing call for mitigation and prevention actions on the role of cleaning and consumer products on childhood asthma.…”
Section: Environmental Pollutants As Determinants Of Childhood Asthmamentioning
confidence: 99%
“…Chlorine bleach or sodium hypochlorite is the most used disinfecting and cleaning agent, and chlorine disinfection by-products (DBPs), such as chlorine or trichloramine, are irritants to the respiratory tract and are also associated with acute lung injury [46]. A recent position paper on the evidence of the health effects of acute and chronic exposure to swimming pools suggested that early and chronic exposure to DBPs may be associated with a higher risk of childhood asthma [47]. Taken together the evidence supports a growing call to mitigation and prevention actions on the role of cleaning and consumer products on childhood asthma.…”
Section: Cleaning and Consumer Products And Childhood Asthmamentioning
confidence: 99%
“…Further, more than 100 DBPs, including trihalomethanes (THMs), haloacetamides, haloketones, haloacetic acids (HAAs), haloacetaldehydes, halonitromethanes, haloacetonitriles (HANs), halogenated cyanogens, halophenols, halobenzoquinones, and Nnitrosamines have been identified in swimming pool water (Richardson et al, 2010;Xia et al, 2012;Weng et al, 2013;Daiber et al, 2016;Li and Blatchley, 2017;Manasfi et al, 2017a). the majority of them are known to have adverse health effects for indoor swimming pool users (swimmers and workers as lifeguards) (Westerlund et al, 2019;Couto et al, 2021;Han et al, 2021;Manasfi et al, 2017b), as being cytotoxic, genotoxic, and mutagenic in vitro or in vivo (Deng et al, 2014;Wagner and Plewa, 2017;Liberatore et al, 2022;Wu et al, 2022). For instance, trichloramine (NCl3) causes the most irritating symptoms (Fantuzzi et al, 2010;Villanueva et al 2015), whereas THMs may cause adverse effects on the reproductive system, liver, kidneys, and nervous system as well as potential long-term risks for the development of cancers (Bessonneau et al, 2011;Zazouli and Kalankesh.…”
Section: Introductionmentioning
confidence: 99%